London. Corresponding-Society, alarm'd. -Vide. Guilty Consciences - Gillray, James, 1756-1815 (Humphrey, H., 1798)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; State arrests; London Corresponding Society; Great Britain -- Politics and government -- 1760-1820